Advice on the self-evaluation process of educational centers - Pérez Aguilar, José Francisco (Avances en Supervisión Educativa, 2013)
Propose in this paper offer advice and guidance on specific aspects of the self that are not fully developed in the current legislation and are demanded by the management teams of schools in the inspection visits to educational tour to them. Considering the pedagogic, organizational and management centers have addressed the timetable for action, the officials responsible for the same and the determination of a set of indicators and instruments that yield information relevant to the situation. The basic ideas of this article are that schools face up the transition from mere preparation and approval of memory or a real self-evaluation process that creates a culture of change and continuous improvement.